Carbohydrate-based label-free detection of Escherichia coli ORN 178 using electrochemical impedance spectroscopy - Guo, Xuefei; Kulkarni, Ashish; Doepke, Amos; Halsall, H Brian; Iyer, Suri; Heineman, William R (Analytical chemistry (Washington), 2012)
A label-free biosensor for Escherichia coli (E. coli) ORN 178 based on faradaic electrochemical impedance spectroscopy (EIS) was developed. α-Mannoside or β-galactoside was immobilized on a gold disk electrode using a self-assembled monolayer (SAM) via a spacer terminated in a thiol functionality. Impedance measurements (Nyquist plot) showed shifts due to the binding of E. coli ORN 178, which is specific for α-mannoside. No significant change in impedance was observed for E. coli ORN 208, which does not bind to α-mannoside. With increasing concentrations of E. coli ORN 178, electron-transfer resistance (R(et)) increases before the sensor is saturated. After the Nyquist plot of E. coli/mixed SAM/gold electrode was modeled, a linear relationship between normalized R(et) and the logarithmic value of E. coli concentrations was found in a range of bacterial concentration from 10(2) to 10(3) CFU/mL. The combination of robust carbohydrate ligands with EIS provides a label-free, sensitive, specific, user-friendly, robust, and portable biosensing system that could potentially be used in a point-of-care or continuous environmental monitoring setting.